2022
DOI: 10.3390/ani12131621
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Composition of Lipids in Forages and the Concentration of Conjugated Linoleic Acid in Cow’s Milk: A Review

Abstract: Conjugated linoleic acid (CLA), has been shown to have protective effects against various diseases, such as obesity, arteriosclerosis, diabetes, chronic inflammatory diseases, and cancer. This fatty acid in ruminants results from two processes, biohydrogenation, which takes place in the rumen, and de novo synthesis, carried out in the mammary gland, and it has linoleic and α-linolenic acids as its precursors. The amounts of precursors in the diets of animals are related to the amounts of CLA in milk. In the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Edible fats from ruminants are the main dietary source of CLA for humans. Some CLA isomers, such as rumenic acid (18:2c9,t11), have health-promoting actions, notably anticancer [ 54 ]. Thus, enrichment of ruminant meat with CLA is often a goal in experiments with growing ruminants [ 27 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Edible fats from ruminants are the main dietary source of CLA for humans. Some CLA isomers, such as rumenic acid (18:2c9,t11), have health-promoting actions, notably anticancer [ 54 ]. Thus, enrichment of ruminant meat with CLA is often a goal in experiments with growing ruminants [ 27 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kliem and Shingfield (2016) have argued that the highest production of CLA occurs in the first third of the lactation period. However, Mojica-Rodríguez et al (2019) have reported that CLA production in milk is not influenced by the lactation status, contradicting the findings of Acosta-Balcazar et al (2022).…”
Section: Introductionmentioning
confidence: 87%
“…The CLA content in milk is influenced by intrinsic factors related to the animal, such as breed, number of lactations and lactation period (Flores et al, 2011;Roca-Fernández et al, 2014;Acosta-Balcazar ABSTRACT. The concentration of conjugated linoleic acid (CLA) in dairy products derived from ruminants, such as cow's milk, is mainly influenced by the dietary lipid profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of vaccenic acid led to the quantity of linoleic acid + α‐linolenic acid consumed and it was the highest in milk from animals fed with a diet containing low polyphenolic content (Ineichen et al ., 2019). The polyphenols from fed are responsible for ruminal linoleic acid and α‐linolenic acid biohydrogenation inhibition, leading to higher amounts of these compounds in mountain milk, the structure of the polyphenol being also relevant (Acosta Balcazar et al ., 2022).…”
Section: Mountain Vs Lowland Dairy Product Chemical Compositionmentioning
confidence: 99%